Spontaneous breathing approach in mild congenital diaphragmatic hernia: A resuscitation algorithm - Emily J. J. Horn-Oudshoorn; Ronny Knol; Suzan C. M. Cochius-den Otter; Arjan B. te Pas; Stuart B. Hooper; Calum T. Roberts; Calum T. Roberts; Neysan Rafat; Thomas Schaible; Willem P. de Boode; Robin van der Lee; Anne Debeer; et al. (Frontiers Media S.A., 2022)
BackgroundInfants with a congenital diaphragmatic hernia (CDH) and expected mild pulmonary hypoplasia have an estimated survival rate of 90%. Current guidelines for delivery room management do not consider the individual patient's disease severity, but an individualized approach with spontaneous breathing instead of routine mechanical ventilation could be beneficial for the mildest cases. We developed a resuscitation algorithm for this individualized approach serving two purposes: improving the success rate by structuring the approach and providing a guideline for other centers.MethodsAn initial algorithm was discussed with all local stakeholders. Afterwards, the resulting algorithm was refined using input from international experts.ResultsEligible CDH infants: left-sided defect, observed to expected lung-to-head ratio ≥50%, gestational age at birth ≥37.0 weeks, and no major associated structural or genetic abnormalities. To facilitate fetal-to-neonatal transition, we propose to start stabilization with non-invasive respiratory support and to adjust this individually.ConclusionsInfants with mild CDH might benefit from an individualized approach for neonatal resuscitation. Herein, we present an algorithm that could serve as guidance for centers implementing this.